Bacterial community composition, quantification of antibiotic resistance genes and antibiotic residues in wastewater treatment plant and receiving rivers - Tsholo, Karabo; Molale-Tom, Lesego; Horn, Suranie; Bezuidenhout, Cornelius Carlos (Frontiers in Microbiology, 2025)
Antibiotic resistance was, until recently, primarily documented as a clinical phenomenon, with limited consideration given to environmental settings in policymaking. Although literature has demonstrated the presence of antibiotic-resistant bacteria in water environments, there is limited information on the concentrations of antibiotic resistance genes (ARGs) and antimicrobial residues, particularly in sub-Saharan Africa. Hence, this study aimed to determine the concentrations of ARGs and antimicrobial residues in urban wastewater effluents and receiving waters in North West Province, South Africa. The physicochemical parameters of the water samples were determined, and the ARGs were screened and quantified using end-point and real-time PCR. Chemical analysis was performed to quantify the concentrations of antibiotics and fluconazole. High-throughput 16S rRNA sequencing was conducted to identify and profile bacterial communities. Correlations between bacterial communities and environmental parameters were determined. Physicochemical parameters indicate that the water quality from wastewater effluent and receiving waters poses no concern for livestock use. However, most were correlated with the presence of distinct microbial communities, of which Proteobacteria and Bacteroidota were the dominant groups. Elevated ARG levels, inducing multidrug resistance, were reported in river water, indicating the longevity and transfer of ARGs in the environment. Notably, river water and wastewater effluent were more contaminated with ampicillin compared to other antimicrobials. The presence of antimicrobials may select for the development of antimicrobial resistance. Despite the widespread presence of ARGs and antimicrobial residues in water environments, these contaminants are not routinely monitored or regulated. The presence of these contaminants in water poses human and ecological risks.